2011
DOI: 10.1007/s10457-011-9406-3
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Baobab (Adansonia digitata L.) fruits’ physical characteristics and nutrient content in the West African Sahel

Abstract: The present study was carried out to evaluate variability in fruit characteristics and nutritional quality of Baobab fruits with the aim of providing the background to select trees bearing fruit with desirable characteristics for further utilisation. Vitamin C, total sugar and ash contents were assessed in 178 Baobab fruit samples from 11 sites in Burkina Faso, Mali and Niger. Furthermore the following tree and fruit physical characteristics were recorded: tree height, bark colour, fruit size, pulp weight, see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
9
18
0
Order By: Relevance
“…Indeed, utilization of the edible leaves as vegetables is important as reported elsewhere (NRC 2006, 2008; Parkouda et al. 2012). Therefore, baobab leaves could be used in food fortification to alleviate malnutrition problems related to micronutrients such as iron and zinc deficiencies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, utilization of the edible leaves as vegetables is important as reported elsewhere (NRC 2006, 2008; Parkouda et al. 2012). Therefore, baobab leaves could be used in food fortification to alleviate malnutrition problems related to micronutrients such as iron and zinc deficiencies.…”
Section: Resultsmentioning
confidence: 99%
“…2005; Parkouda et al. 2012). However, there are few data on the variation of the biochemical composition of baobab leaves, and much less on their age–age correlation (mother trees compared to progenies).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buchmann et al [7] reported about 300 traditional uses of baobab in Africa. The baobab fruit weighs between 150 and 350 g in Senegal, and can reach more than 496 g in Niger [9].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that fruit chemical composition vary between natural populations, for example in V. paradoxa (Maranz et al 2004), but generally there is little knowledge on factors controlling yield and quality of parkland fruit trees. Parkouda et al (2011) demonstrate that A. digitata fruit weight and concentrations of vitamin C and sugar vary between and within populations. The variation correlated with precipitation, latitude and longitude of the populations, indicating regional differences in the chemical composition of the fruits.…”
Section: Variation In Fruit Quality and Quantitymentioning
confidence: 85%